Rights and entitlements of a foreign spouse to the deceased's estate under the Malaysian law of succession - Halim, Akmal Hidayah (Sweet & Maxwell Asia, 2010)
A valid marriage will undoubtedly give rise to some mutual rights between the husband and the wife. Such rights include a right to property under the law of succession which arises upon the death of the spouse. Under the Malaysian law of succession, such a right will be legally recognized if there is proof as to the marital relationship that is normally determined based on a marriage certificate issued upon registration of such a marriage. Nevertheless, in some cases of cross-border marriages, it is very unlikely for the parties to register their marriage due to non-citizenship of the foreign spouse or that the foreign spouse being an illegal immigrant. It is also a requirement that such a spouse, in order to be entitled to succession, should have the legal capacity to own Malaysian property. The requirements are rather strict in cases of property involving land which is subject to some restrictions and prohibitions as stipulated in the Malaysian National Land Code 1965. In light of these circumstances, this article seeks to analyse the rights and entitlements of a foreign spouse, particularly under the Malaysian law of succession. It is important that the appropriate legal constraints be ascertained to ensure that in the event of death, the interests of the foreign spouse would not in any manner be adversely affected or prejudiced.